Cultural Differences of Apology Strategies Employed by Western and Eastern Influencers on Social Media - Yeni Marlia wardani; Pariyanto Pariyanto; SHARMINI ABDULLAH (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the apology strategies used by social media influencers in written public apologies following incidents of public criticism and cancel culture. The phenomenon of the online ‘apology clarification’ has become a recognizable communicative genre, yet not all such statements meet the criteria for a sincere apologetic speech act. Grounded in Speech Act Theory (Searle, 1969) and the apology strategy taxonomy of Cohen and Olshtain (1981) as further developed by Trosborg (1995), this research adopts a descriptive qualitative, case-study design to analyze written apology statements posted on X (Twitter) and Facebook by five influencers, two representing an Eastern (Indonesian) cultural background and three representing a Western (American) cultural background. The data were interpreted through the lens of Brown and Levinson’s (1987) Politeness Theory to explain how each strategy functions to protect the speaker’s face. The findings show that all six apology strategies appeared across the data, with influencers consistently combining at least three strategies within a single statement rather than relying on one. Acknowledgement of Responsibility and Expression of Apology (IFID) emerged as the most frequently used strategies overall, while Minimization of the Offense appeared more selectively and was associated with lower perceived sincerity. Cultural patterning was also evident: Indonesian influencers favored repeated, polite expressions of regret oriented toward preserving social harmony, whereas American influencers favored explicit acknowledgment of responsibility paired with detailed, self-protective explanation. These findings contribute to pragmatic research on digital discourse by demonstrating how apology strategies function simultaneously as face-saving devices and as culturally shaped communicative practices in the era of cancel culture.